The Role of Optical Coherence Tomography Angiography in Non-Arteritic Ischemic Optic Neuropathy: A Case Report - Syntia Nusanti; Brigitta Marcia Budihardja; Lazuardiah Anandi; Rona Ali Badjrai (Majalah Oftalmologi Indonesia, 2022)
Introduction: Non-arteritic ischemic optic neuropathy (NAION) is the second most common optic neuropathy in adults. Since circulatory insufficiency is presumed to have a role in pathogenesis of NAION, optical coherence tomography angiography (OCTA) is suggested as a tool in assessing NAION patients, while optical coherence tomography (OCT) can detect structural changes. This case report aims to describe the congruity of visual field defect with OCT and OCTA result in a case of bilateral NAION, highlighting the role of both OCT and OCTA in NAION. Case Report: A 52-years-old male came due to painless, progressive blurry vision in both eyes, especially in lower visual field, for the past 7 months. Humphrey visual field examination revealed inferior visual field defects in both eyes. OCTA showed reduced retinal perfusion in the superior part bilaterally. OCT revealed ganglion cell loss in the superior part of his right eye and almost all parts of his left eye. Retinal nerve fiber layer (RNFL) thinning was found in the superior part bilaterally. Discussion: In this case, the congruity of visual field defect, reduced perfusion, ganglion cell-inner plexiform layer (GCIPL), and RNFL thinning portrayed the connection of hypoperfusion as the presumed underlying mechanism of NAION, neuron loss as the result of the hypoperfusion, and the visual field loss as the presenting symptom in NAION. Conclusion: This finding demonstrates the role of OCT-A and OCT in diagnosing and monitoring progression in patients with NAION.OCT-A is a useful tool to evaluate microvascular changes, while OCT can be used to evaluate RNFL and GCIPL thinning.